Introduction to marine engineering - Taylor, D. A., M. Sc
This second edition deals comprehensively with all aspects of a ship's machinery from propulsion and steering to deck machinery and electrical equipment with a strong emphasis upon correct and safe procedures. Material has been added and revised to reflect the greater weight now being placed upon the cost-effective operation of ships; in terms of greater equipment reliability, more fuel-efficient engines, the ever-increasing shift towards automatically operated machinery, and the need for fewer engineering crew. This is an invaluable guide for professionals but equally covers the requirements for Class 4 and Class 3 Engineer's Certificates of Competency, the first two years of the Engineer Cadet Training Scheme, and the Engineering Knowledge syllabus for the Master's Certificate.